(untitled) (Revista Brasileira de Contabilidade e Gestão, 2022)
Objective(s): The study aims to relate the usefulness and functions of the budget in the decision-making process, based on the perceptions of the managers of a company in the metal-mechanical sector. Method: Methodologically, the research is descriptive, based on a survey, considering a sample of 33 managers/supervisors/analysts who work in different areas of the studied company. Results: It was found that 78.80% of managers use the annual budget with monthly monitoring (budget versus actual), 84.80% indicate its use as an artifact of planning, coordination, resource allocation, and determination of operational volumes. The mean rank (MR) obtained shows that managers identify the functions of budget planning, dialogue, and utility, demonstrating the usability of the instrument in the management process. The main functions of the budget were identified as: the coordination of the company’s units (4.82); analysis of monthly and annual projections (4.76); planning linked to company strategies (4.73); and comparison of planned performance with actual results (4.70); the results even indicate that in the context of the COVID-19 pandemic, the budget helped to align new strategies and adjust organizational planning (4.27). The findings indicate that the budget has multiple functions for the managers of the company studied, confirming its recognition by managers as a management instrument, with utility related to the planning and decision-making processes. Contributions: As a contribution, the study highlights the different functions and adaptability of the budget in the organizational context, demonstrating its usability by managers who work in different sectors in the company.